Théorie de l’esprit et communication chez les primates non-humains - Laure Legrain (Revue de Primatologie)
The question of the existence of a theory of mind in non-human primates was raised over 30 years ago and today, the debate remains open. The difficulty of finding a consensus probably comes from the fact that theory of mind is not a monolithic ability but involves different kinds of mental states. Through a literature review we will assess the possible implication of these different mental states in communicative exchanges of nonhuman primates. We will consider the principle of intentionality in various communication contexts. We will then analyze the role of joint attention in pointing gesture and its direct link with the ability to shared attention. Finally, we will discuss how some primates are able to adapt their behavior to ignorance they attribute to others, however without being able to ascribe them false belief.